RUSSIAN WRITING CENTERS CONSORTIUM - E. M. Bazanova; I. B. Korotkina (Высшее образование в России)
Newly established academic writing centers in leading Russian universities have to respond to both institutional and methodological challenges. At the core of these challenges is a lack of awareness among the Russian scholarly community of academic writing as a separate branch of scientific and methodological knowledge in addition to insufficient number of specialists, inadequate training and rare publications in this field. Founded in 2016, the Russian Writing Centers Consortium (WRCC) aims to provide networking and professional development opportunities to writing center professionals. The article highlights aims and objectives of the Consortium, describes first steps towards their implementation and the prospects for further development of the organization.